Evaluation of Tensile Properties and their Correlation with Microstructural Characteristics of a Closed Die Forging of Iso-symmetrical Aerospace Grade Ti-6Al-4V Alloy - Majila, Anuradha Nayak; Fernando, D. Chandru; Babu, S.N. Narendra; Patnaik, B.V.A.; Prasad, N.E. (Defence Science Journal, 2015)
<!– P margin-bottom: 0.21cm; direction: ltr; color: rgb(0, 0, 0); line-height: 115%; widows: 2; orphans: 2; P.western font-family: "Calibri",sans-serif; font-size: 11pt; P.cjk font-family: "Calibri",sans-serif; font-size: 11pt; P.ctl font-family: "Times New Roman",serif; font-size: 11pt; –> In the present technical paper an iso-symmetrical forging in titanium alloy, i.e., Ti-6Al-4V is chosen for cut-up evaluation and study of mechanical properties and their correlation with microstructural characteristics. Tensile test specimens were extracted from rim, web and bore regions of the forgings aligned in radial and tangential directions. Test specimens varying from various locations were extracted to conduct the tests (ASTM E8) at various temperatures from room temperature to 300 °C. Statistical analyses of the tested data were carried out to quantify the variation in tensile properties along rim, web, and bore regions at room temperature. Effects of radial and tangential alignments of specimens at room temperature was also studied. Among the different test specimens, the specimen that exhibited mechanical properties close to average values were further subjected to microstructural and fractographic investigations using optical and scanning electron microscopes. These studies revealed that there is a marginal inhomogenity in the microstructure of the forgings and this variation controls the mechanical properties and fracture characteristics of the material. Microstructure marginally varies from rim to bore region. Similarly, along the thickness of the forging, there is a small variation in the microstructure. The aforementioned correlations have established the fact that the microstructure variations from different locations and among different specimen orientations have resulted in mild variation in the tensile properties. Defence Science Journal, Vol. 65, No. 2, March 2015, pp.171-178, DOI:http://dx.doi.org/10.14429/dsj.65.7232